2016
DOI: 10.1536/ihj.15-319
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Genes and MicroRNAs Associated With Atrioventricular Septal Defect in Down Syndrome Patients

Abstract: SummaryDown syndrome (DS) is a common chromosome 21 abnormality disease, leading to various health problems, especially atrioventricular septal defect (AVSD). Genes and microRNAs (miRNAs) associated with AVSD in DS patients still need in-depth study.Gene expression data (GSE34457) of 22 DS patients without congenital heart disease and 7 DS patients with AVSD were downloaded from Gene Expression Omnibus. After screening differentially expressed genes (DEGs) based on limma package in R (criteria: P < 0.05 and |l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…STRING (version 11.0) 7 , is a freely accessible database, that collects, scores, and integrates data, is used to predict functional relationships between proteins (Szklarczyk et al, 2019). A PPI network of the DEGs with combined score >0.4 in STRING was considered as a functional link, and was constructed using the Cytoscape software (version 3.7.2) 8 (Smoot et al, 2011;Wang et al, 2016aWang et al, , 2018Li et al, 2017;Zhao et al, 2019). Subsequently, we used the MCODE plugin to identify densely connected modules from the PPI network with the criteria of K-core = 2, degree cutoff = 2, max depth = 100, and node score cutoff = 0.2 (Bandettini et al, 2012).…”
Section: Protein-protein Interaction Network Construction and Module mentioning
confidence: 99%
“…STRING (version 11.0) 7 , is a freely accessible database, that collects, scores, and integrates data, is used to predict functional relationships between proteins (Szklarczyk et al, 2019). A PPI network of the DEGs with combined score >0.4 in STRING was considered as a functional link, and was constructed using the Cytoscape software (version 3.7.2) 8 (Smoot et al, 2011;Wang et al, 2016aWang et al, , 2018Li et al, 2017;Zhao et al, 2019). Subsequently, we used the MCODE plugin to identify densely connected modules from the PPI network with the criteria of K-core = 2, degree cutoff = 2, max depth = 100, and node score cutoff = 0.2 (Bandettini et al, 2012).…”
Section: Protein-protein Interaction Network Construction and Module mentioning
confidence: 99%
“…26 The genes outside chromosome 21, CRELD1 has been found to participate in AVSD development in DS patients. 27,28 Recent studies attempted to investigate the basic biological association of cardiac anomalies with DS through overexpression of chromosome 21 microRNAs (miRNAs). 29 However, the mechanism of CHD development in DS is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, two studies [ 13 , 14 ] confirmed that genes NKX2-5 , GATA4 , and CREL1 participate in the pathogenesis of AVSD in DS. In 2016, another study [ 15 ] focusing on all types of genetic contribution on AVSD in DS showed that not only the genetic variants but also other regulatory variants (e.g., altered microRNA expression) may participate in such pathogenesis. As a specific form of genetic variants, copy number variants (CNVs) have been widely identified in DS according to many recent publications.…”
Section: Introductionmentioning
confidence: 99%